2014
DOI: 10.1016/j.landusepol.2013.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Assessing policy tools for encouraging farm afforestation in Ireland

Abstract: Some rights reserved. For more information, please see the item record link above.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 44 publications
1
31
0
1
Order By: Relevance
“…Most studies analyze the effectiveness of government programs supporting the afforestation of farmland. They are often based on the results of surveys addressing farmers, who are asked to describe the key drivers and the main obstacles in the afforestation process [16,20,21,30], or institutions supporting afforestation schemes [19]. Regression models are developed, and marginal effects of forestry subsidies are calculated [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies analyze the effectiveness of government programs supporting the afforestation of farmland. They are often based on the results of surveys addressing farmers, who are asked to describe the key drivers and the main obstacles in the afforestation process [16,20,21,30], or institutions supporting afforestation schemes [19]. Regression models are developed, and marginal effects of forestry subsidies are calculated [18].…”
Section: Discussionmentioning
confidence: 99%
“… In weakly developed regions and in areas affected by a crisis where agriculture is the only available source of income, afforestation could create new jobs during stand establishment, tree maintenance, timber preparation for sale (In Poland, farmers can achieve and sell timber after receiving permission from relevant forest inspectorate; usually only for the trees that are 90-120 years old), etc. [20].  Farmland conversion has an associated opportunity cost (loss of income resulting from farmland conversion).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the role of extension and communication are crucial in the development of knowledge, perceptions and attitudes about on-farm tree planting (Meijer et al 2015). According to existing models, farmers' decision making about on-farm tree planting is motivated by their objectives (Duesberg et al 2013, Duesberg et al 2014, Gasson 1973, Siebert et al 2006, Willock et al 1999, Zubair and Garforth 2006. The outcome variable in these models is the farmer's tree planting and management activities.…”
Section: Farmer Motivation and Decision-making Theorymentioning
confidence: 99%
“…Thus, it is essential to understand the factors that motivate farmers to plant and manage on-farm trees. In the literature, socio-psychological factors, such as perceptions and attitudes, have been studied to explain adoption behaviour of farmers in relation to on-farm tree planting (Duesberg et al 2013, Duesberg et al 2014, Fischer and Vasseur 2002, Meijer et al 2015, Mekoya et al 2008). For instance, Zubair and Garforth (2006) studied the perceptions and attitudes of farmers in Pakistan and showed that the farmers' willingness to grow trees on their farms was a function of their attitudes towards the advantages and disadvantages of growing trees.…”
Section: Introductionmentioning
confidence: 99%